Study on Acute Leukemia in Iraqi Population - Mohammed, Taghreid; Abed, Najlaa; Al-khalidy, Saja; Al-rubaiy, Khaled (Iraqi Journal of Science, 2025)
Many children under 15 years of age and many adults more then 15 Years of age with acute leukemia registered and treated in Oncology Department attached to the Al- Yarmuk Teaching Hospital, Child Central Hospital and air force Hospital in Baghdad were enrolled in this study, as regards to their general characteristics and the type of scute leckemia. For comparison purposes, one year was chosen (2000), it was showed that the incidence with ande lymphoblastic leukemia in children was 72.5%, while the Incidence with acute myelocytic leukemia in adults was 27.55. During this year, 2000, male predominance was evident. The fraction of patients living in urban areas was more than these of ranal regions The symptoms of leukemia patients we hesitate, vomiting, anemia, and fever (38- 38.5°C) the mere than 2 weeks fever pallive, spleen of liver were moderately enlarged or hepatosplenomegalys in addition to throat and mouth lestons Mest children and adult also has thrombocytopenia, leucopenia and high rate of erythrocyte sedimentation rate menal characteristic of acute leukemia in this study were compared to these repose wher